Oeuvres Physiologiques, Volume 2 - Le Cat, Claude-Nicolas (Chez Vallat-La-Chapelle, 1767)
The second of three volumes by Claude-Nicolas Le Cat (1700-1768), a French surgeon, lithotomist, researcher, and science communicator. Volume two was originally published as the Traité des sens in Rouen in 1740, though—seeing as the pagination began at 201—it was always envisioned as part of the larger work. The work of which this eventually became the second volume did not appear until a full 27 years after its initial publication and at Paris rather than Rouen, though the plates and a number of the sheets are identical, indicating that the publisher still had what was left of the first printing. By that time, the first volume had swelled to over 200 pages, so the pagination between the first two volumes is inconsistent, and Le Cat had composed a lengthy addendum to volume two. By volume three he abandons any attempt at continuity and starts the pagination over at 1. The volumes discuss the anatomy and physiology of the sense organs - the eyes, ears, nose, tongue, and skin. Digitization of this work includes the frontispiece, title page, two chapter opening pages with engravings, and 14 plates.
Keywords: Senses and sensation; Sense organs; Physiology; Le Cat, Claude-Nicolas, 1700-1768; Vision; Hearing; Smell; Touch; Taste